RELATIONAL AESTHETIC DALAM DUNIA SENI KONTEMPORER - Alvi lufiani (Ars: Jurnal Seni Rupa dan Desain, 2008)
Relational aesthetic identified by a Tranch theorist and cumtor, Nicolas Bourriaud, has been anemerging art movement that consistent in fudging artworks on the basis o f the inter human relationso f which they represent or produce. Instead o f the artists' capability, the Relational aesthetic places theaudiences or viewers to be the key factor fo r the success o f an exhibition or performance. The number o fcontemporary artists who exercise performative and interactive techniques- which rely on others, evensometimes strangers- is growing. Without any participation from the others, there will be no art -worksprotluced.A critical thought from an art history professor, Claire Bishop, makes the development o f therelational aesthetic in the art worid even more dynamic, both socially and artistically. She studied what typeo f relation being engaged, fo r whom and fo r what reasons.Keywords: relation, audience, participation